Update on Novel Therapies for Pancreatic Neuroendocrine Tumors - Oberstein, Paul Eliezer; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Neuroendocrine tumors (NETs) describe a heterogeneous group of tumors with a wide range of morphologic, functional, and behavioral characteristics. Pancreatic neuroendocrine tumors (pNET) are a subset of NETs which are increasing in incidence and prevalence. These tumors are generally slow growing and behave in an indolent fashion. However, when these tumors spread they can be life threatening and difficult to treat with current modalities. In 2011, the landscape of treatment for pNET was changed with the approval of two targeted agents, sunitinib and everolimus, the first new therapies for this disease in over 20 years. Data from these clinical trials and extensive preclinical work into the underlying molecular pathways in neuroendocrine tumors has generated intense interest in the quest to identify additional effective agents in this challenging disease. At the 2012 American Society of Clinical Oncology (ASCO) Annual Meeting, several researchers presented updated data regarding the use of targeted agents, alternative chemotherapeutic agents and combinations of these in the treatment of pNET. Corrie et al. (Abstract #4121) reported data from a chemotherapy clinical trial replacing 5-FU with capecitabine and evaluating the addition of cisplatin in NETs. Several authors reviewed the addition of the anti VEGF monoclonal antibody bevacizumab into combination therapy. Ducreux et al (Abstract #4036) presented results from a trial of chemotherapy plus bevacizumab while Firdaus et al. (Abstract #4127) reported the results of combination therapy with octreotide, bevacizumab, and pertuzumab. Hobday et al. (Abstract #4048) reported positive results of an interim analysis of combination therapy with an mTOR inhibitor and bevacizumab. Kulke et al (Abstract #4125) reported the results of a clinical trial utilizing an antibody targeting the insulin growth factor receptor. Finally, Vinik et al. (Abstract #4118) provided updated survival data form the seminal phase III trial that led to approval of sunitinib in the treatment of pNET. The authors review and summarize these abstracts in this article. Image: Bard Haven Towers, Columbia University Medical Center. New York City, NY, USA (Autumn time).